YOGA IS ALTERNATIVE SYSTEM OF MEDICINE : AN A EMPIRICAL STUDY - Sunitha H. E (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This paper made an attempt study on "Empirical things on yoga as alternative system of medicine". Study will undoubtedly helps for academicians and yoga practitioners.